Alytaus miesto architektūra prieškariu - Mačiulis, Algimantas (Journal of Architecture and Urbanism, 2010)
Pre-war architecture of Alytus town During a couple of hundred years, a mixed-plan system has been formed in Alytus: an irregular one in the old town and exact and rational in the new town parts, based on a regular street network, correct plan and spatial structure. Historical factors determined the town’s development: on the right bank of the Nemunas river the development was slow (Alytus I), and the center of the town, formed on the left bank of the Nemunas river (Alytus II), from the urban point of view, was the most valuable part of the town. The period 1930–1940 was extremely important for the town’s development: central areas were arranged, quite a number of public buildings were built (town hospital, tuberculosis sanatorium, town municipality, seminary, etc.), a reinforced concrete bridge over Nebulas. In 1935–1944 Vytautas Trečiokas, the chief architect and designing engineer of Alytus district, tried to make Alytus look like a holiday resort and designed a modern elementary school. Article in Lithuanian. Santrauka. Straipsnyje aptariama Alytaus miesto architektūra prieškariu, istorinės aplinkybės, kai miestas, pradėjęs kurtis dešiniajame Nemuno krante, menkai plėtojosi (I-as Alytus), o miesto branduolys, jo centras susiformavo upės kairiajame krante (II-as Alytus). Prieškariu II-me Alytuje šalia senamiesčio kūrėsi nauji rajonai – Naujamiestis, Kurortas. 1930–1940 m. – Alytaus augimo dešimtmetis, miestas plėtėsi ir vystėsi kaip vasarvietė. Pažymėtina Alytaus apskrities ir miesto vyriausiojo inžinieriaus, architekto Vytauto Trečioko veikla, jo prieškariu projektuoti visuomeniniai ir privatūs gyvenamieji namai, tarp jų moderni Alytaus pradinė mokykla Nr. 4 Birutės g. 26. Reikšminiai žodžiai: miesto planinė erdvinė sistema, mišri plano struktūra, miesto įvaizdis, miesto ir gamtos ryšys. First Published Online: 22 May 2013